How Brand Reputation Influences Customer Satisfaction: A Case Study of Starbucks, Malaysia - Aryani, Dwi Nita; Singh, Padmalini; Liew, Yee Wen; Kee, Daisy Mui Hung; Li, Yurou; Li, Jiahui; Lim, Choon Yan; Arif, Wibowo (AIBPM Publisher, 2021)
Starbucks has a lot of loyal consumers from all over the world. There are some reasons that consumers tend to purchase at Starbucks. This study examines the influences of brand reputation on customer satisfaction in Starbucks, Malaysia. The study adopted a survey research design. The method of data collection in this study are internet sources and questionnaires. A total of 100 respondents participated in this survey. The data were analyzed with descriptive statistics and inferential statistics. From the findings of the study, we find out that the aspects of brand reputation influence and correlate to customer satisfaction in Starbucks, Malaysia. Besides, some recommendations for Starbucks' improvement can be obtained through the findings.